Ecuadorian infant mortality linked to socioeconomic factors during the last 30 years - Natalia Romero-Sandoval; Diego Del Alcázar; Jacob Pastor; Miguel Martín
Abstract Objectives: to analyze the difference among geographical units and the evolution of infant mortality rate (IMR) based on Ecuadorian censuses (1990-2001-2010). Methods: artificial Neural Network analyzed the impact of sociodemographic factors over the variability of IMR. Poisson regression analyzed the variation of the standardized IMR (sIMR). Results: the decrease in the national IMR was 63.8%; however, 42.8% provinces showed an increase in 2001-2010. The variability was explained mainly by illiteracy decrease. The adjusted RR between provincial sIMR with illiteracy and poverty revealed a trend towards the unit. Conclusions: the variation of IMR reflects a complex interaction of the sociodemographic factors.